2018
DOI: 10.3389/fmicb.2018.00751
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Avian β-Defensin 2 Is Possibly Mediated by the p38 MAPK Signal Pathway in Chicken Embryo Fibroblasts After Newcastle Disease Virus Infection

Abstract: The study was conducted to evaluate whether avian β-defensins (AvBDs) could be induced by Newcastle disease virus (NDV) infection, and to investigate the potential signaling pathway of AvBD2 induction in response to NDV infection as well. First, mRNA expression of AvBDs (1–14) was evaluated in the chicken embryo fibroblasts (CEFs) infected with NDV strain F48E9 at 6, 12, 24, 36, and 48 h post-inoculation (hpi), respectively. The results demonstrated a significant induction of AvBD2 in CEFs elicited by the NDV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 71 publications
(106 reference statements)
0
14
0
Order By: Relevance
“…In addition, AvBD12 induced migration of murine immature dendritic cells. Futhermore, mRNA expression of AvBD2 was upregulated with Newcastle disease virus infection in chicken embryo fibroblasts through p38 MAPK-dependent manner ( Liu et al., 2018 ). Yang et al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AvBD12 induced migration of murine immature dendritic cells. Futhermore, mRNA expression of AvBD2 was upregulated with Newcastle disease virus infection in chicken embryo fibroblasts through p38 MAPK-dependent manner ( Liu et al., 2018 ). Yang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Also, AvBD12 induced migration of murine immature dendritic cells. Also, mRNA expression of AvBD2 was upregulated with Newcastle disease virus (NDV) infection in chicken embryo fibroblasts through p38 MAPK-dependent manner [43]. Yang et al [16] demonstrated that human β-defensin-2 induced chemoattraction of CD4+ memory T cells and immature dendritic cells, by binding to CCR6.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory activity of a test compound against influenza virus infection-induced death of MDCK cells was measured by CPE reduction assay using CCK-8 as previously described ( Choi et al, 2016 ; Wang et al, 2017 ; Jin et al, 2018 ; Liu et al, 2018 ). PBS containing no inhibitor and the anti-influenza virus agent, Favipiravir (T-705), were included as the negative and positive controls, respectively.…”
Section: Methodsmentioning
confidence: 99%